Juridical analysis of the involvement of the Indonesian National Army in countering criminal acts of terrorism criminal acts of terrorism - Wawan Hermawan; Soerya Respationo; Erniyanti Erniyanti; Fadlan Fadlan (Dynamics of Politics and Democracy, 2022)
Purpose: The purpose of this research is to find out the implementation of the involvement of the Indonesian National Army in countering criminal acts of terrorism to realize order in society and national sovereignty, to find out what factors are obstacles and solutions to the involvement of the Indonesian National Army in countering criminal acts of terrorism to realize order and national sovereignty. Research methodology: The research method used is normative juridical (legal research) through literature studies with an empirical juridical approach (sociological juridical) through field studies aimed at obtaining legal knowledge empirically. Results: The results showed that the implementation of the role of the Indonesian National Army Kepri in preventing criminal acts of radicalism is by conducting early detection in order to find out all changes in social life in society and its further development, identifying the nature of threats that are and will be faced, then providing early warnings as basic material and determining directions for policy and decision making or action by Indonesian National Army leaders. Implementation: Factors inhibiting the performance of the Indonesian National Army of Riau Islands region in conducting early detection of efforts to prevent criminal acts of terrorism include poor human resources (HR) both from the quantity and quality of Indonesian National Army Kepri members, facilities, infrastructure, and budget financing of Indonesian National Army activities in preventing criminal acts of terrorism, lack of understanding of the terrorism movement. While the solution to these problems is to build and foster intelligence networks, as well as optimizing tasks and functions with special education and as supervisors in deradicalization programs and conducting counseling to the public about radicalism.